Pneumococcal Carriage Among Indigenous Kichwa Children From the Ecuadorian Andes After the 10-Valent Pneumococcal Vaccine Introduction. Issue 11 (7th September 2021) - Regalado L, Daniela; Rivera-Olivero, Ismar A.; Garcia-Bereguiain, Miguel Angel; Tana, Leandro; Hernandez, Isabel; Zurita, Jeannete; Vidal, Jorge E.; Terán, Enrique; de Waard, Jacobus H.
Abstract : Background: We assessed nasopharyngeal pneumococcal carriage in Andean Kichwa children, the largest Amerindian indigenous population in the Ecuadorian Andes. All children in our study had been vaccinated with the 10-valent pneumococcal vaccine (PCV10). Methods: Nasopharyngeal swabs from 63 families, 100 children <10 years old including 38 children under 5 years and 63 adult caregivers, from 5 different communities, were cultivated for Streptococcus pneumoniae and isolates were serotyped and antibiotic susceptibility testing was performed. Results: Respectively, 67% of the 38 children under 5 years old, 49% of the 62 children between 6 and 10 years old and 16% of the 100 adults were colonized with S. pneumoniae . Of these, 30.9% carried a vaccine serotype, 5.4% a serotype shared by the PCV10/13-valent pneumococcal vaccine (PCV13) vaccine and 25.5% a PCV13 serotype or PCV13 vaccine-related serotype, with 19A (10.9%) and 6C (10.9%) as the most prominent. Drug susceptibility testing revealed that 46% of the S. pneumoniae strains were susceptible to 6 tested antibiotics. However, 20.3% of the strains were multidrug-resistant or extensively drug-resistant strains, including 82% of the vaccine (-related) serotype 19A and 6C strains. Conclusions: Kichwa children, vaccinated with PCV10, were highly colonized with pneumococci and should be considered a high-risk group for pneumococcal disease. Twenty-five percent of the colonizing S. pneumoniae strains were PCV13-only vaccine-targeted serotypes, and in addition to that, most were multidrug-resistant or extensively drug-resistant strains. The vaccine benefits for this population possibly will significantly increase with the introduction of PCV13.